ATM networks : - Kasera, Sumit (McGraw-Hill, 2007)
ATM (Asynchronous Transfer Mode) is a breakthrough networking technology. It provides a single platform for voice, video and data, driving network convergence, all with very high quality of service. This book provides a comprehensive, engineering-level introduction to ATM networks. It explores fundamental concepts in detail, explains and illustrates the 3 levels of the ATM protocol reference model, details the process of internetworking with LANs and WANs, as well as IP, and covers all major ATM applications.